Batman & Robin. Year one - Waid, Mark, 1962- (DC Comics, 2025)
"Bruce Wayne has adopted Dick Grayson and found a partner in his war on crime, but making both relationships work may be the greatest challenge Batman and Robin have ever faced. And when a mysterious new crime boss called the General declares war on Gotham City's mob families, the lives of far more than just the Dynamic Duo depend on their partnership coming together!" -- page [4] of cover.